Die tekskritiek van die Nuwe Testament (1): Die huidige metodologiese situasie - Jacobs, L. D. (Verbum et ecclesia, 1991)
The textual criticism of the New Testament (1): The current methodological Situation This first article in a two-part series on the textual criticism of the New Testament focuses on the current state of affairs regarding textcritical methodology. Majority text methods and the two main streams of eclecticism, viz moderate and rigorous eclecticism, as well as statistical methods and the use of conjectural emendation, are reviewed with regard to their views on method as well as the history of the text. The purpose is to arrive at a workable solution which the keen and often not so able textual critic, translator and exegete can use in his handling of the Greek text of the New Testament.